Labour supply responses to fiscal reforms in Portugal: An illustration with recent PIT and child benefit reforms - Edlira Narazani; Sara Riscado; Lara Wemans (European Commission, Joint Research Centre (JRC), 2024)
In the last decade, two major disruptions - the Great Recession and the Covid sanitary crisis - hit the world economy and gave rise to a battery of government measures. In Portugal, after the fiscal consolidation efforts implemented to tackle the severe sovereign debt crisis that accompanied the Great Recession, some restrictive fiscal measures were reversed. Throughout and after the pandemic crisis, fiscal measures maintained their expansionary nature, with reinforcements to child benefits and income tax cuts. This paper quantifies the distributional and labour market impacts of policy changes implemented on the income tax system and on the child benefit in Portugal in 2022 and 2023. First-order effects of these measures, quantified using the EUROMOD microsimulation model, reveal that changes to the income tax schedule exhibit a regressive pattern, whereas those affecting the minimum untaxed income were more evenly distributed. In contrast, the child benefit reinforcements show a progressive impact. Employing EUROLAB, a behavioural labour supply and demand model, we find that labour supply responses are relatively modest, due to the small direct impacts of the measures on disposable income. Overall, labour supply, both in terms of hours of work and participation, reacts positively to the tax breaks but negatively to the reinforcement of the child benefit, with this negative reaction being concentrated on specific income and gender groups, such as single parents with children or families in lower income quintiles.
Keywords: 330